Sinergi 4 Pilar Penegakan Hukum Dalam Memberikan Perlindungan hukum Terhadap Korban Kekerasan Dalam Rumah tangga - Mahdy; Samsul Arifin (Academos, 2025)
Law enforcement against domestic violence (DV) is a crucial aspect in ensuring protection for victims. In the Indonesian legal system, law enforcement is supported by four main pillars of law enforcement: the Police, the Prosecutor's Office, the Courts, and Advocates. These four pillars play a crucial role in providing legal protection for victims of domestic violence in accordance with Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU-PKDRT). This study employed a normative juridical method with a statute approach and a review of other relevant literature. The results indicate that although regulations explicitly regulate victim protection, implementation in the field still faces various obstacles, such as a lack of understanding of gender perspectives among law enforcement officials, limited access to legal assistance by victims, and a lack of coordination between relevant institutions. Furthermore, the role of the four pillars of law enforcement in addressing domestic violence still requires strengthening, both in terms of regulations, enforcement mechanisms, and synergy between institutions. This study concludes that the effectiveness of legal protection for victims of domestic violence depends heavily on optimizing the role of the four pillars of law enforcement and improving the implementation of existing policies. Reform efforts are needed in the form of increasing the capacity of legal officials, wider outreach regarding victims' rights, and strengthening sector coordination so that legal protection can run more optimally.